Language Editors: Job Prestige, Influence on Language and Perceived Threats - Jakaitė-Bulbukienė, Kristina; Micutaitė, Neringa (Lietuvių kalba, 2023)
The object of this work is to analyse Lithuanian language editors‘ self-assessment of their own work, to see how they are influenced by societal attitudes, and to uncover their relationship to Lithuanian language. These aspects help to investigate the linguistic attitudes of Lithuanian language editors. This is analysis of 10 qualitative in-depth semi-structured interviews with Lithuanian language editors. The texts edited by the participants vary in their nature. All informants are women. Nine interviews have been conducted orally and one in writing. The method applied is qualitative content analysis of the interviews. It has been found that the informants of the study feel that there are critical, skeptical attitudes towards language editors and linguists in general in the public sphere. Editors also often hear inaccurate assessments of their profession from inner cycle. However, most of them do not take such attitudes seriously and do their work without taking them into account. It has been found that most of the informants feel that they contribute to the development of the Lithuanian language and that they influence the language. This is because even editors with extensive editing experience are constantly confronted with new phenomena. Most of the informants of this study have told they can edit freely, are trusted by clients or writers, and are not constrained making their decisions. Editors have also answered that they have a mission to enrich and purify language. A small number of informants of the study have told that they do not see themselves as language creators, but only as executors of the already established language policy. Some editors have indicated they want to stop the influence of English to Lithuanian, while others believe that the influence of other languages is a natural phenomenon, and stress that the language is impoverished by an excessive desire to purify it.
Keywords: language editors; linguistic attitudes; job prestige; influence on language; threats to language